Effect of fasting and refeeding on expression of genes involved in the gastric nutrient sensing and orexigenic control of pigs. Issue 4 (10th December 2014) - Priori, D.; Trevisi, P.; Mazzoni, M.; Messori, S.; Bosi, P.
Summary Knowledge on orexigenic signals in the pig stomach is poor. Gastric amino acid sensing by taste receptor type 1 member 3 (T1R3) and calcium‐sensing receptor (CASR), and active ghrelin release, controlled by preproghrelin, proprotein convertase (PC1/3) and ghrelin O‐acyltransferase (GOAT) genes, may be affected by fasting or refeeding. Twelve pigs (12.0 kg LW) were adapted to a base diet and assigned to three individual feeding schedules: Control (C), fed twice a day; Fasting (F), fasted for 24 h; Refeeding (R), fasted for 24 h and refed before slaughtering. Gastrointestinal segments were collected for histology and molecular biology analyses. Total RNA isolated from oxyntic and pyloric mucosae was reverse transcribed, specific porcine primers were designed and transcript quantification was performed by real‐time RT‐PCR. F decreased villus height in duodenum (p < 0.01) and ileum (p < 0.05) vs. C and R. R increased oxyntic PC1/3 (p < 0.05) and tended to increase oxyntic preproghrelin (p = 0.06), and pyloric GOAT (p = 0.07) gene expression vs. C. PC1/3 gene expression was higher in pyloric mucosa. Ghrelin‐positive cells numbers were not different between the two gastric mucosae. Gastrin expression tended to be higher in R than in C and F (p = 0.068 and p = 0.055). CASR was higher in pyloric than in oxyntic mucosa, and pyloric CASR expression tended to be higher in R than in C (p = 0.072). T1R1 was not affected by treatment. Our results indicate that the pool of genes involved in the secretion of active ghrelin is active both in oxyntic and pyloric mucosa of pig. Refeeding can significantly affect the expression of genes that control octanoyl‐ghrelin production and partially the amino acid sensing by CASR gene, while the absence of effect of fasting on the expression of ghrelin‐related genes needs further confirmations.